FSH and TSH in the Regulation of Bone Mass: The Pituitary/Immune/Bone Axis - Graziana Colaianni; Concetta Cuscito; Silvia Colucci (Clinical and Developmental Immunology)
Recent evidences have highlighted that the pituitary hormones have profound effects on bone, so that the pituitary-bone axis is now becoming an important issue in the skeletal biology. Here, we discuss the topical evidence about the dysfunction of the pituitary-bone axis that leads to osteoporotic bone loss. We will explore the context of FSH and TSH hormones arguing their direct or indirect role in bone loss. In addition, we will focus on the knowledge that both FSH and TSH have influence on proinflammatory and proosteoclastogenic cytokine expression, such as TNFα and IL-1, underlining the correlation of pituitary-bone axis to the immune system.